Contemporary Art as a Social Reflection: an Approach to the Artwork of Regina José Galindo - Otárola Guevara, Marcela (2021)
Contemporary art emerges in the 20th century and stands out for the change of a paradigm, derived from a new way of linking the artist and society. In order to appreciate such relationship, it is proceeded to qualitatively analyze some works of an exponent of this movement, Regina José Galindo, from a questioning and later interpretation on the reasons that have originated her productions, exercise that required studying theoretical premises coming from sociology, philosophy and history of art. The selected pieces refer to themes associated with memory, women and power relations; they show empathy and spatial appropriationas mechanisms of social articulation and reveal the scope of her proposals: to expose oppressed people, to question the viewer and to give value to the context.